Rab3 GTPase-activating protein regulates synaptic transmission and plasticity through the inactivation of Rab3 - Sakane, Ayuko (National Academy of Sciences, 2006)
Rab3A small G protein is a member of the Rab family and is most abundant in the brain, where it is localized on synaptic vesicles. Evidence is accumulating that Rab3A plays a key role in neurotransmitter release and synaptic plasticity. Rab3A cycles between the GDP-bound inactive and GTP-bound active forms, and this change in activity is associated with the trafficking cycle of synaptic vesicles at nerve terminals. Rab3 GTPase-activating protein (GAP) stimulates the GTPase activity of Rab3A and is expected to determine the timing of the dissociation of Rab3A from synaptic vesicles, which may be coupled with synaptic vesicle exocytosis. Rab3 GAP consists of two subunits: the catalytic subunit p130 and the noncatalytic subunit p150. Recently, mutations in p130 were found to cause Warburg Micro syndrome with severe mental retardation. Here, we generated p130-deficient mice and found that the GTP-bound form of Rab3A accumulated in the brain. Loss of p130 in mice resulted in inhibition of Ca(2+)-dependent glutamate release from cerebrocortical synaptosomes and altered short-term plasticity in the hippocampal CA1 region. Thus, Rab3 GAP regulates synaptic transmission and plasticity by limiting the amount of the GTP-bound form of Rab3A.